2011
DOI: 10.1111/j.1549-8719.2011.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcations: Focal Points of Particle Adhesion in Microvascular Networks

Abstract: Objective Particle adhesion in vivo is dependent on microcirculation environment which features unique anatomical (bifurcations, tortuosity, cross-sectional changes) and physiological (complex hemodynamics) characteristics. The mechanisms behind these complex phenomena are not well understood. In this study, we used a recently developed in vitro model of microvascular networks, called Synthetic Microvascular Network, for characterizing particle adhesion patterns in the microcirculation. Methods Synthetic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 34 publications
(41 reference statements)
2
34
0
Order By: Relevance
“…A programmable syringe pump (PHD 2000, Harvard Apparatus, MA) was used to inject the particles and the flow was set for a shear rate of 240 1/sec. Every 3 min, the flow was reduced by half reaching a final shear rate of 7.5 1/sec, similar to our previous studies (Doshi et al, 2010; Kolhar et al, 2013; Lamberti et al, 2013; Prabhakarpandian et al, 2011c, 2001; Sakhalkar et al, 2003). The new shear rate was maintained for 3 min to allow sufficient time for a statistically significant number of adhesion events to occur (Doshi et al, 2010; Kolhar et al, 2013; Lamberti et al, 2013; Prabhakarpandian et al, 2011c; Smith et al, 2014).…”
Section: Methodsmentioning
confidence: 68%
See 3 more Smart Citations
“…A programmable syringe pump (PHD 2000, Harvard Apparatus, MA) was used to inject the particles and the flow was set for a shear rate of 240 1/sec. Every 3 min, the flow was reduced by half reaching a final shear rate of 7.5 1/sec, similar to our previous studies (Doshi et al, 2010; Kolhar et al, 2013; Lamberti et al, 2013; Prabhakarpandian et al, 2011c, 2001; Sakhalkar et al, 2003). The new shear rate was maintained for 3 min to allow sufficient time for a statistically significant number of adhesion events to occur (Doshi et al, 2010; Kolhar et al, 2013; Lamberti et al, 2013; Prabhakarpandian et al, 2011c; Smith et al, 2014).…”
Section: Methodsmentioning
confidence: 68%
“…Previously, our group has shown that the presence or absence of endothelial cells and/or receptor concentrations on their surfaces, are not the driving forces behind the preferential adhesion patterns of neutrophils near bifurcations (Prabhakarpandian et al, 2011c; Rosano et al, 2009; Tousi et al, 2010). Similar to our previous results (Lamberti et al, 2013), the number of adherent particles/neutrophils in junction regions is statistically higher than in straight sections depending on local shear stress.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These devices termed SynVivo-Synthetic Microvascular Networks (SMN) are developed using PDMS based soft-lithography process. SynVivo-SMN devices can be used to obtain shear adhesion map of cell/particle adhesion 22 , study targeted drug delivery 23 and have been validated against in vivo data [24][25] Representative Results Figure 1A shows a schematic and a bright field image of SynVivo-SMN device. Figure 1B shows the SynVivo-SMN device mounted on a glass slide.…”
Section: Introductionmentioning
confidence: 99%